Strengthening Da'wah Amidst the High Use of Tiktok Media in Bima City, West Nusa Tenggara - Nurmiati; Akhmad Rifa’i (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Tiktok media is audio-visual media that presents various creative and interesting content and information for users. This media has become a popular application that is widely used and downloaded throughout the world. The high rate of use of TikTok media is like two sides of a coin which has an impact on various vulnerable ages, especially children. Children are an age that is vulnerable to being exposed to the impact of TikTok media in the era of the tsunami of content that is increasingly emerging, especially regarding their religious behavior. This article aims to determine the strengthening of da'wah amidst the high use of media among children in Ntobo Village, Raba District, Bima City. This research uses a qualitative approach with descriptive methods. The data was obtained through observations, interviews and documentation. Based on this research, it is known that the high use of TikTok media tends to have a negative impact on children's religious behavior which can be seen from various forms of deviation from religious law, a decrease in moral values and politeness and an increasing sense of shame. In this case, strengthening the value of da'wah is a solution to stem the tsunami of TikTok media content which is supported by parental supervision and social control.